The relationship between empowerment and job burnout in auxiliary health workers in 2019 - Nasrin Shokrpour; Leila Bazrafkan; Marzieh Talebi (Wolters Kluwer Medknow Publications, 2021)
INTRODUCTION: Health-care workers in community service professions are the formerly candidate for occupation burnout. This study aimed to investigate the relationship between empowerment and job burnout among auxiliary health workers (behvarzan) at Fasa University of Medical Sciences. MATERIALS And METHODS: In this descriptive-analytical study, 120 auxiliary health workers were enrolled using the census. Spritzer's psychological empowerment and Maslach burnout inventory questionnaires were used to collect the data. Then, they were analyzed through the SPSS software, using descriptive analytical tests. RESULTS: The findings of this study revealed that the auxiliary health workers' empowerment was in the range of 22-75 with a mean ± standard deviation [SD] of 48.5 ± 9.71, which is in a fairly high level considering the highest score (75) in this scale. Moreover, with respect to burnout (mean ± SD of 58.03 ± 18.64), 36 participants (30%) had low level of burnout, 69 subjects (57.5%) were at the intermediate level, and 15 (12.5%) suffered high levels of job burnout. According to the results of this study, there were a high correlation and negative relationship (r = 0.406, P > 0.001) between psychological empowerment and job burnout among the auxiliary health workers. On the other hand, all empowerment components (competence, autonomy or independence, effectiveness, and trust) had a reverse and significant association with burnout. CONCLUSION: Based on the results of this study, the auxiliary health workers (behvarzan) were in a good range of empowerment; also, the dimensions of empowerment were correlated with job burnout in Fasa university-affiliated hospitals' health workers. On the other hand, demographic features had no association with these two factors. It is suggested that health authorities should take measures to empower the workers and identify and remove the effects of the various dimensions of job burnout among the health workers in these hospitals.